Visualization of 3D rock mass properties in underground tunnels using extended reality. Issue 1 (March 2021) - Janiszewski, M; Uotinen, L; Szydlowska, M; Munukka, H; Dong, J; Rinne, M
Abstract: The term extended reality (XR) refers to a family of technologies that cover Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR). The main benefit of XR is that it can offer a new viewpoint on the surrounding environment by augmenting it with digital data and visualizations. Recent developments of XR enable its deployment for rock engineering applications, including underground tunnels. In this paper, we demonstrate two cases of the use of XR in an underground tunnel to display spatial information on the tunnel surface. One of the tunnels in the Underground Research Laboratory of Aalto University (URLA) was digitized using Structure-from-motion (SfM) photogrammetry. As a result, a high-resolution 3D point cloud and textured model of the tunnel were created. Next, the rock joint planes were obtained semi-automatically from the digitized rock surfaces. The results are then represented in their actual positions in the tunnel geometry. In the first case, we used VR to display the rock joint planes on the textured model of the tunnel. In the second case, the data was displayed in real-time in tunnel conditions through a mobile device. The results demonstrate that XR technology can be successfully used in underground construction to digitize the workplace and provide a new perspective on the work environment, which can potentially lead to an increase in safety and productivity.